A double-lined spectroscopic binary in the open cluster Trumpler 14 - Levato, Orlando Hugo (2000)
We present the results of a determination of the preliminary orbital elements of the spectroscopic binary FMM 3 in the field of the open cluster Trumpler 14. The spectrum of this binary shows two sets of lines that are roughly similar. The period found was around 5 days (P = 5.0339 ± 0.0003), and the orbit is eccentric (e = 0.51 ± 0.02). These values were adopted from the combined solution for both components. The mass ratio of the system is 0.76 ± 0.06.